Identifying the Naphthalene-Based Compound 3,5-Dihydroxy 2-Napthoic Acid as a Novel Lead Compound for Designing Lactate Dehydrogenase-Specific Antibabesial Drug - Yu, Long; Zhan, Xueyan; Liu, Qin; Sun, Yali; Li, Muxiao; Zhao, Yangnan; An, Xiaomeng; Tian, Yu; He, Lan; Zhao, Junlong (Frontiers in Pharmacology, 2020)
Human babesiosis is caused by apicomplexan Babesia parasites, including B. microti, B. crassa, B. sp. MOI, B. divergens, B. duncani and B. venatorum. Among them, B. microti is the most common-cause of human and rodent babesiosis, and is frequently accompanied by high parasitemia. No available vaccine is recommended and drugs for treatment of the disease are associated with high failure rate and side effect. As B. microti lacks a traditional TCA cycle and dominatingly relies on anaerobic metabolism to produce ATP, we suspect that B. microti lactate dehydrogenase (BmLDH), a key glycolytic enzyme, plays a critical role in B. microti ATP supply. Herein, BmLDH was expressed in E. coli BL21 with a ~37 kDa size. Enzyme activity inhibitory experiments show that DBHCA and DHNA inhibit rBmLDH catalysis with ~111-fold and ~5000-fold selectivity over Human LDH, respectively. SPR assays demonstrate that DHNA has a lower KD to BmLDH (3.766 x 10-5 M), but DBHCA reveals a higher affinity (3.988 x 10-8 M). Comparing the kinetic parameters (ka and kd values), we observe that DBHCA bind the target faster than DHNA, while the complex of DHNA with the target dissociate slower than that of DBHCA. Interestingly, DBHCA and DHNA inhibit the growth of B. microti in vitro with IC50 values of 83.23 and 76.43 μM. Cytotoxicity tests in vitro further indicate that DBHCA and DHNA have selectivity indexes (SI) of 2.7 and 25.3 between B. microti and Vero cells, respectively. Although the two naphthalene-based compounds only display modest inhibitory activity both against rBmLDH and growth of B. microti, the compound DHNA with high selectivity could be a candidate for designing LDH-specific anti-babesial drug.